Uji Validasi dan Reliabilitas Instrumen Penilaian Kemampuan Berpikir Kritis Siswa Kelas VI Sekolah Dasar - Maryono Maryono (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This research aims to determine content validity and reliability. Critical thinking assessment instruments that previously existed. The instrument developed is in the form of test questions. Analysis of the test items used the V coefficient by Aiken's while reliability was estimated using Kappa with the help of SPSS Version 28. The results showed that the test questions and research questions proved valid, the highest with Aiken's V coefficient ?s, namely 0.841 and reliable with a Cronbach Alpha coefficient of 0.903. After being validated, it was then tried out on class VI students at Karangtengah 01 Elementary School. The trial results showed that the level of difficulty of spreading and the differential power had good average criteria (can be used). Based on the results of this study, the instrument for assessing the critical thinking skills of class VI students at SDN Karangtengah 01 is valid and practical.